Osadnictwo pradziejowe Wysoczyzny Świeckiej - Grabarczyk, Tadeusz (Acta Universitatis Lodziensis. Folia Archaeologica, 1994)
The actual state of research on this mezoregion is presented and special attention paid to the reconstruction of the natural environment by means of paleobotanical methods. The earliest traces of human occupation date there from the close of the Middle Stone Age (Mesolithic), followed by absence of any occupation. Next settlements did not occur until the Bronze Age. The settlement of the Pomeranian culture is the best recognized (32 cemeteries). Archaeological finds as well as the evidence of pollen diagrams suggest that econological conditions during the Bronze Age were particularly favourable for stock breeding and less for farming. In the Roman period the two ways of procuring food became equal in proportion. The area of the Świecie Upland was „retarded” in cultural development since certain prehistoric cultures, notably the Chojnice-Pieńki and perhaps also the Pomeranian culture could have survived there longer than it is generally accepted. Due to inadequate penetration of the mezoregion in question, the picture of prehistoric community is, however, far from being full.